Use of Screen Real Estate on University Home Pages. - Zinoviev, Alexander (My University, 2008)
In this project, the home pages of the 11 comprehensive universities in the University of Wisconsin System were analyzed and compared according to categories suggested by Jakob Nielsen. This research clearly defines eight categories of screen real estate and then uses them to compare home pages of each university. Results show that the universities do not use space efficiently and that they vary according to how they use their Web sites for such things as promoting themselves or providing content of interest. Design suggestions are offered for improving the allocation of screen real estate on university home pages: use design that takes advantage of the entire screen; allocate more space to content of interest and navigation; and limit use of self promotion content and filler.
Oshkosh Scholar, Volume 3, 2008 pp. 64-72
Keywords: Nielsen, Jakob; Web page design; Web sites -- Design